Biosynthesis and Kinetics of Silver Nanoparticles Formation by Reduction using Banana Kepok (Musa balbisiana) Peel Extract - Wara Dyah Pita Rengga; Dhimas Setiawan; Khosiatun Khosiatun (Department of Chemical Engineering, Universitas Gadjah Mada, 2018)
Biosynthesis and silver nanoparticles formation during the reduction of AgNO3were carried out by using an aqueous peel extract of banana kepok (Musa balbisiana) asa stabilizing agent. The formation of the stable silver nanoparticles with differentconcentration of AgNO3 has resulted in mostly spherical particles. The Ultraviolet-Visiblespectrophotometer, Transmission Electron Microscopy, X-Ray Diffractometer were usedto characterize these biosynthesized silver nanoparticles. The spherical shapednanoparticles were uniformly distributed with the range diameter of 5 to 50 nm and theparticles were naturally crystallized with the crystal structure of the face-centered cubicgeometry. Additionally, the kinetics of the formation process of silver nanoparticles wasobserved by the UV-Vis spectrophotometer. Based on the kinetic functions, the reductionprocess of banana peel extract had a constant formation rate of the autocatalytic processat 4.35 x 10-4/s.